Research on the Influence of Economic Policy Uncertainty on Stock Market Heterogeneity Based on Investor Perspective - Liu, Ting (Journal of Accounting, Business and Finance Research, 2019)
For the investors in the Chinese stock market, it is mainly divided into institutional investors and individual investors. It is well known that the number of individual investors, that is, the shareholding ratio, occupies the vast majority of the stock market, so changes in their investment behavior and sentiment will inevitably have a profound impact on the stock market. Although the proportion and size of institutional investors is smaller than that of individual investors, because of the concentration of funds and the concentration of investment behavior, the stock market will also play a non-negligible role. This paper will analyze from the perspective of investors in the stock market, whether the behavior of different investor entities has different degrees and different effects on stock market volatility. Through analysis, it is found that when the proportion of institutional investors increases, the volatility of corporate stocks can be effectively reduced. Volatility in corporate stocks rises when investor sentiment is high. When considering the shareholding ratio of institutional investors and investor sentiment, economic policy uncertainty has a greater impact on corporate stock volatility.